Analisis Tingginya Kandungan Minyak Hasil Proses Oily Water Separator di Kapal KM. Dophin Nusantara 2 - Rukmini; Agus Adib Prabowo; Muhammad Yusuf; Sufriyadi; Supardi Temmu (Politeknik Pelayaran Barombong, 2023)
The Oily Water Separator is an auxiliary equipment on a ship capable of separating oil from oily air discharge until the separation reaches less than 15 ppm through filtration and density difference. On board the vessel KM. DOLPHIN NUSANTARA 2 owned by PT. PELAYARAN BERJAYA NUSANTARA, the writer conducted research on the OWS from TAIKO KIKAI type USC-03, which is a machine used to filter bilge water before discharging it into the sea. There was an issue where the oil content produced by the OWS exceeded the limit set by MARPOL, which is 15 ppm, triggering an alarm indicating excessively high oil content. The writer conducted a 9-month and 3-day-long research, starting from November 15, 2020, until August 18, 2021. The data obtained was directly from the research object, the Oily Water Separator, and involved direct maintenance conducted with the engineer overseeing and guiding when trainees were directly involved in the maintenance or repair work. Additionally, documentation related to the thesis title was included. The results obtained from this research indicated that the increase in oil content in the Oily Water Separator's output was due to the dirtiness of the filters within the system and a lack of understanding regarding the operation of these filters, thus resulting in the elevated oil content. ABSTRAK Oily Water Separator adalah peralatan pendukung kapal yang dapat memisahkan minyak dari buangan udara yang mengandung minyak sampai hasil pemisahannya kurang dari 15 ppm selama proses filtrasi dan perbedaan berat jenis. Penulis melakukan penelitian di kapal KM. DOLPHIN NUSANTARA 2 yang dimiliki oleh PT. PELAYARAN BERJAYA NUSANTARA yang menggunakan mesin bantu OWS TAIKO KIKAI type USC-03 untuk menyaring air got sebelum dibuang ke laut mengalami masalah. Kandungan minyak dalam mesin bantu OWS melebihi batas MARPOL sebesar 15 ppm yang menyebabkan alarm menyala yang menunjukkan bahwa kandungan minyak melebihi batas. Penelitian ini dilakukan selama sembilan bulan tiga hari, atau dari tanggal 15 November 2020 hingga 18 Agustus 2021. Data yang dikumpulkan berasal dari penelitian langsung pada Oily Water Separator dan perawatan langsung pada objek penelitian, dengan masinis membantu dan mengawasi saat taruna melakukan perbaikan atau perawatan langsung. Selain itu, ada file dokumentasi yang berkaitan dengan judul penelitian. Studi ini menemukan bahwa kotornya saringan saluran dan ketidaktahuan tentang cara mengoperasikannya menyebabkan kandungan minyak meningkat dalam proses pemisah air kotor.